Ball Dribbling Optimization of Basic Skills Through Play Method In Football Athletes Age 8-10 Years SSB rosary 2018: Ball Dribbling Optimization of Basic Skills Through Play Method In Football Athletes Age 8-10 Years SSB rosary 2018 - Fajar Mugo Raharjo; Pedomanta Keliat (Institute Of Computer Science (IOCS), 2020)
This study aims to improve the results of the exercise dribble through exercise bermainpada SSB athletes ages 8-10 years TASBI Medan 2018. Subjects in this study were 8-10 years of age athlete TASBI Terrain SSB numbered at least 21 people who will be given the act a form of exercise in the form of practice dribbling through practice methods of playing. To obtain the data in this study is the observation sheet dribbling technique. The data analysis technique used is the data reduction and exposure data. After the data collected and the analysis of the obtained results: the results of pre-test observation data obtained 21atlet (100%) who scored the results of observation with an average of 56.14%. From the results of the exercise cycle I obtained 19 athletes (90.47%), which has reached mastery exercises, and who have not achieved mastery exercise value, gained 2 athletes (9.53). With the average value of the observation of the first cycle is 86,50%. In this case it can be seen that an increase in the average value of the results of the exercise significant between the pre-test athletes to cycle I. Based on the results of data analysis can be said that through the implementation of the exercise bermaindapat improve workout results dribble in athletes aged 8-10 years SSB Terrain TASBI 2018.